Alarms and Their Outcomes in Left Ventricular Assist Device Patients. Issue 12 (December 2021) - Lim, Zi Z.; Robson, DesireE; Muthiah, Kavitha; Jansz, Paul; Macdonald, Peter S.; Hayward, Christopher S.
Abstract : Low flow and suction alarms are provided to alert caregivers of changes in left ventricular assist device pump function but may be reset in clinical practice. We investigated the incidence and underlying causes of these alarms as well as their prognostic significance. HeartWare ventricular assist device patients (n = 113) were divided into quartiles based on their frequency of low flow and suction alarms. Survival and adverse events (thrombus, stroke, bleeding, and right heart failure) were compared between quartiles. Low flow alarms peaked in the first few months of pump support before dropping down to near negligible levels. Suction alarm frequency remained relatively constant throughout pump support. Although pump speeds ( p < 0.001) and flow ( p = 0.01) decreased over time, there was an increase in suction alarm frequency ( p = 0.018), with no changes in low flow alarms. Patients with smaller body size ( p = 0.016) and lower pump flows ( p = 0.008) had higher frequencies of low flow alarms on multiple regression ( p < 0.001). Patients with the highest low flow alarm frequency demonstrated poorer survival ( p = 0.026). There was no relationship between suction alarm frequency and survival. There was also no relationship between either low flow or suction alarm frequency with strokes, gastrointestinal bleeds, pump thrombus, or right ventricular failure. Duration of alarm and intervention in response to the alarm was not assessed in this study. Further studies examining alarm duration and responses may inform future pump alarm algorithms. Abstract : Supplemental Digital Content is available in the text.